On reverse representation - Joubert, Gideo (Stellenbosch : Stellenbosch University, 2025)
Joubert, Gideo. 2024. On reverse representation. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131689